Factors Related to the Behavior of Using IUD Contraceptives in Women of Childbearing Age in The Koto Baru Health Center Work Area, Sungai Penuh City in 2021 - Ramah Hayu (Science Midwifery, 2022)
Population growth in Indonesia is always increasing. Until now, Indonesia is still ranked fourth in the world. One effort to overcome the population problem is to participate in the Family Planning (KB) program, but the prevalence of using the IUD method in 2015-2017 in developing countries has decreased even though the effectiveness of the IUD is 97-99% in preventing pregnancy and long-term use. This type of research is descriptive analytic with a cross sectional approach. The population in this study were all women of childbearing age in the working area of ​​the Koto Baru Health Center as many as 651 people with proportional random sampling technique with a sample of 87 people. The results showed that out of 87 respondents, 68 (78.2%) did not use an IUD, 74 (85%). did not receive husband's support as many as 61 (.70.1%) and the quality of family planning services was not good 64 (73.6%). From the chi square statistical test the relationship between knowledge and husband's support with IUD contraceptive use behavior p-value = 0.000, while the statistical test of the relationship between family planning service quality and IUD contraceptive use behavior p-value = 0.002.